Growth Rate, Carcass Weight and Percentage Weight of Carcass Parts of Laying Type Cockerels, Kampong Chicken and Arabic Chicken in Different Ages - Tamzil, M.H.; Ichsan, M.; Jaya, N.S.; Taqiuddin, M. (Pakistan Journal of Nutrition, 2015)
This study was designed to determine the effect of age of laying-type cockerels, kampong chicken and arabic chicken on growth performance, carcass weight and the percentage weight of carcass parts. The experiment was designed in a Complete Randomized Design with 3 x 7 factorial arrangements. The first factor was types or lines of chicken consisted of 3 levels i.e., laying-type cockerels, kampong chicken and arabic chicken. The second factor was age of slaughtering consisted of 7 levels i.e., at the ages of 4, 5, 6, 7, 8, 9 and 10 weeks. The study used 63 day old chick (DOC) laying-type cockerels, 63 unsexed DOC kampong chickens and 63 unsexed DOC arabic chickens. Each line of chicken was divided into 9 groups consisted of 7 chicks. Every group was kept in a one meter cubic cage. Every weekend, feed intake and body weight were measured. At the end of the fourth week, from each group, one chicken was randomly selected for measurement of live weight, carcass weight and the percentage weight of carcass part. The results of the study found that laying-type cockerel, kampong chicken and arabic chicken had the same feed intake and feed efficiency, but had different body weight gains, carcass weights and the percentage weight of carcass parts (drumstick, thighs, wings, breast and back). The increase of age affected feed intake, body weight gain, feed efficiency, carcass and the percentage weight of carcass part. There was an interaction between the line of chicken and age on body weight gain, but there was no interaction on feed intake, feed efficiency, carcass weight and the percentage weight of carcass part (drumstick, thighs, wings, breast and back).